Anti-Semitic Catholic press in Costa Rica: the case of Eco Católico and La Época (1933-1941) - Pérez-Navarro, Ricardo A. (2025)
This essay analyzes the anti-Semitic discourse of the Catholic press in the Eco Católico and La Época in Costa Rica between 1933 and 1941. The aim is to comprehend the catholic dogmatism in the (re)production and spread of antisemitism within the Costa Rican Catholic society.